All geared towards success? Cultural origins of gender gaps in student achievement - Helena Holmlund; Helmut Rainer; Patrick Reich (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
Although geographical and temporal variations in gender achievement gaps have received considerable attention, the role of culture in explaining this variation is not well understood. We exploit a large Swedish administrative data set to study gender gaps in education among second-generation immigrant youth with different cultural backgrounds. Guided by hypotheses we derive from the economics literature on gender differences and gender convergence, we explore the predictive power of a set of cultural dimensions including achievement orientation, acceptance of inequality, risk avoidance, and long-term orientation. Our empirical strategy relies on within-family, cross-gender sibling comparisons, identifying culture's differential impact on girls relative to boys while netting out unobserved family heterogeneity. We find that the central cultural dimension that matters for gender gaps in student achievement is the extent to which a society emphasizes ambition, competition, and achievement, which is strongly predictive of a relative achievement disadvantage of girls compared with boys. Exploring factors that may explain the results, we find that parents from achievement-oriented cultures choose higher quality schools for their children, and that boys benefit more from exposure to higher quality schools than girls do. Using PISA data to probe external validity, we find qualitatively and quantitatively remarkably similar results in a very different sample of second-generation immigrant youth.
Keywords: 330; Culture; Achievement Orientation; Gender Gaps in Education